Stabilizer-Guided Inhibition of Protein-Protein Interactions - Milroy, Lech-Gustav; Bartel, Maria; Henen, Morkos A.; Leysen, Seppe; Adriaans, Joris M. C.; Brunsveld, Luc; Landrieu, Isabelle; Ottmann, Christian (Angewandte Chemie, 2015)
The discovery of novel protein–protein interaction (PPI) modulators represents one of the great molecular challenges of the modern era. PPIs can be modulated by either inhibitor or stabilizer compounds, which target different though proximal regions of the protein interface. In principle, protein–stabilizer complexes can guide the design of PPI inhibitors (and vice versa). In the present work, we combine X‐ray crystallographic data from both stabilizer and inhibitor co‐crystal complexes of the adapter protein 14‐3‐3 to characterize, down to the atomic scale, inhibitors of the 14‐3‐3/Tau PPI, a potential drug target to treat Alzheimer’s disease. The most potent compound notably inhibited the binding of phosphorylated full‐length Tau to 14‐3‐3 according to NMR spectroscopy studies. Our work sets a precedent for the rational design of PPI inhibitors guided by PPI stabilizer–protein complexes while potentially enabling access to new synthetically tractable stabilizers of 14‐3‐3 and other PPIs. Die Entwicklung eines Inhibitors von Protein‐Protein‐Wechselwirkungen wurde von der Kokristallstruktur eines Protein‐Stabilisator‐Komplexes geleitet. Der wirksamste Inhibitor der Bindung von 14‐3‐3 an das phosphorylierte Volllängen‐Tau‐Protein wurde biochemisch und biophysikalisch analysiert. Er hat eine neuartige molekulare Struktur, die spezifisch in die Inhibitor‐Stabilisator‐Schnittstelle von 14‐3‐3 bindet.